RESISTENSI PEREMPUAN BALI PADA SEKTOR INDUSTRI KREATIF DI DESA PAKSEBALI, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Widiastiti, Anak Agung Istri Putera (E-Jurnal Kajian Budaya (Online Journal of Cultural Studies), 2013)
Gender’s of distinguished male and female as a result of development social construction in society effect to subordination female. That is seems in sector development creative industry at Paksebali’s village. Claim job will happen only for a male, meanwhile female job result are qualify tend on by its character helping their husband job only. That is bring on unsatisfactory among female worker, it has been impacted going on resistensi’s action. Farther, this research intended to know the forms, understanding of motivate factors, and to understand impact and interpreting the meaning of resistensi’s Bali female on sector creative industry at Paksebali’s village.
Keywords: resistensi, Balinese female, equivalence